2017
DOI: 10.1007/s00415-017-8498-8
|View full text |Cite|
|
Sign up to set email alerts
|

Muscle MRI in neutral lipid storage disease (NLSD)

Abstract: Neutral lipid storage disease (NLSD) is a rare inherited disorder of lipid metabolism resulting in lipid droplets accumulation in different tissues. Skeletal muscle could be affected in both two different form of disease: NLSD with myopathy (NLSD-M) and NLSD with ichthyosis (NLSD-I). We present the muscle imaging data of 12 patients from the Italian Network for NLSD: ten patients presenting NLSD-M and two patients with NLSD-I. In NLSD-M gluteus minimus, semimembranosus, soleus and gastrocnemius medialis in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Whole body CT-scan and lower limb muscle MRI were obtained following a previously described protocol according to international consensus recommendation [ 6 ].…”
Section: Methodsmentioning
confidence: 99%
“…Whole body CT-scan and lower limb muscle MRI were obtained following a previously described protocol according to international consensus recommendation [ 6 ].…”
Section: Methodsmentioning
confidence: 99%
“…or Sudan Black staining (Figure 2). Muscle MRI has a role in diagnostic assessment [8]. The whole-body study showed involvement of muscles gluteus minimus, semimembranosus, soleus and gastrocnemius medialis in the lower limbs and infraspinatus in the upper limbs were the most affected muscles, with a specific pattern of muscle involvement with “patchy” areas of fatty replacement, while mm.…”
Section: Diseasesmentioning
confidence: 99%
“…Cellular functional studies can contribute to clarifying the residual enzymatic activity of one specific enzyme in particular cases [6]. The role of MRI, a largely used method of studying myopathies, is still not completely investigated in lipid myopathies but some papers have been published for specific myopathies, as neutral lipid storage disease (NLSD), MTP and Very-Long-Chain Acyl-CoA Dehydrogenase (VLCAD) [7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 50 cases of NLSDM have been reported worldwide from a range of various ethnic groups [1, 35, 8, 14, 20] including Chinese [10, 12, 21, 22]. However, NLSDM patients are typically described from a few families in case reviews [1, 3, 4, 8, 14, 20] or in small cohorts of patients [4, 5, 16]. The rarity and broad geographical distribution of NLSDM limits a comprehensive understanding and prompt diagnosis of this disease, and the phenotype/genotype correlation remains unclear [3, 4, 15, 20].…”
Section: Introductionmentioning
confidence: 99%